Health Promotion Behavior, Daily Activities, and Perceived Transportation Problems of Elderly People Living in a Small Town for from the Nearest Train Station - Yoshimoto, Teruko; Kawata, Chieko (Nihon Rōnen Igakkai zasshi, 1998)
We examined sex and age differences in health promotion behavior, participation in social activities, and perceived transportation problems of elderly people living in a small town far from the nearest train station. A questionnaire was sent to 567 men and women aged 60 years old and over living in a small town in Kanagawa prefecture. A total of 397 people responded. The questionnaire consisted of 42 questions concerning their health, daily activities (including their desire to participate in social activities), the frequency with which they went out, their attitude toward health promotion behavior, and their perceived transportation problems. They were also asked why they acted in ways that promote their health. The reliability of the data was examined with the coefficient κ and with Cronbach's alpha. Chisquared tests were used to examine sex and age differences. Women reported more health problems and more transportation problems, and said that they were less active in social activities than did men. Women become inactive in daily life with increasing age earlier than do men. Contrary to our hypothesis, women tended to have medical examinations more often than did men. More women under 75 years old than men answered that they acted in ways that promote their health because they did not want to give others trouble when they became ill, fewer women than men said that they wanted to enjoy their intended activities. These results seem to show that women lead less active social lives than do men and have less motivation for promoting their health because of a desire to lead an active life.